Associations of nutrient intake, dietary behaviours, and patterns with metabolic profiles and obesity measures: findings from a cross-sectional study in a southern Chinese population - Chen, Yifan; Chen, Guanlin; Liang, Yinglin; Huang, Haiyan; Cai, Yefeng; Ni, Xiaojia (Frontiers in Nutrition, 2025)
BackgroundMetabolic diseases and obesity are highly prevalent, and diet plays a key role in their prevention and management. This study aimed to characterise the nutrient intake, dietary behaviours, and patterns of the South Chinese population and examine their associations with metabolic profiles and obesity measures.MethodsData for this study were obtained from a cross-sectional study involving participants residing in Guangdong Province, China. Demographic information, disease history, nutrient intake, and dietary behaviours were collected via face-to-face interviews using structured questionnaires. Metabolic profiles and obesity levels were assessed via clinical laboratory tests, physical examinations, and bioelectrical impedance analysis. Principal component factor analysis (PCFA) was used to identify dietary patterns, while descriptive statistics, correlation analysis, and binary logistic regression were employed to characterise diets and assess their associations with metabolic profiles and obesity measures.ResultsA total of 330 participants were included in this study, with a mean age of 53.62 years. Males accounted for 50.9% of the participants. The majority of participants preferred rice as their staple food and regularly consumed fresh vegetables. Red meat was frequently eaten, while white meat was consumed often. Seafood, legumes, and Cantonese soup were consumed occasionally, whereas traditional Chinese ultra-processed foods such as dairy and pasta were rarely consumed. Three distinct dietary patterns were identified in the study. The modern Cantonese dietary pattern was characterised by the consumption of white meat, eggs, milk, aquatic products, fresh fruits, vegetables, and Cantonese slow-cooked soup. The traditional Cantonese dietary pattern was defined by a high intake of traditional Chinese ultra-processed foods. Meanwhile, the localised Western dietary pattern featured the consumption of pasta, breakfast foods, coffee, and Cantonese desserts. The modern Cantonese dietary pattern was associated with a lower likelihood of dyslipidaemia than the traditional Cantonese dietary pattern, while the localised Western dietary pattern was linked to a reduced likelihood of glucose metabolism disorders and visceral obesity. Notably, these associations remained significant even among participants without a prior diagnosis of diabetes.ConclusionThis study characterised the dietary patterns of the South Chinese population and found that modern Cantonese dietary patterns appeared to be associated with lower odds of dyslipidaemia, while localised Western dietary patterns were potentially linked to a reduced likelihood of glucose metabolism disorders or visceral obesity.